Kabat interventions integrated with facial expressive and functional exercises for better and speedy recovery in bell’s palsy; a pre-post design - Adhikari, Shambhu Prasad; Chaudhary, Manisha; Dev, Rubee (Journal of Chitwan Medical College, 2020)
Background: Bell’s palsy (BP) is an acute and idiopathic paralysis of the seventh cranial nerve, which has higher incidence rate in Asian countries compared to the western world. Different contemporary physiotherapy interventions have been used in treatment of impairments and functional limitations caused due to the BP. However, traditional usual care is still in practice in context like Nepal, which has to be shifted to evidence-based treatment. Therefore, present study investigated effectiveness of Kabat intervention integrated with facial expressive and functional exercises in Bell’s palsy. Methods: This pre-post comparative study recruited eight participants of age 22 to 52 years with acute and sub-acute, unilateral, idiopathic BP by purposive sampling. A physiotherapist administered the Kabat intervention integrated with facial expressive and functional exercises for four weeks. Another physiotherapists assessed before as well as after two and four weeks of the treatment using Sunny Brook Facial Grading, House-Brackmann grading, lip-length measurement, facial disability and patients’ satisfaction measures. One-way ANOVA with repeated measures was used to analyze data across three points of time. Results: Eight participants with mean age 41.38 years (10.66) completed the study. Significant improvement with high effect sizes (0.82 – 0.95) was found on both outcome measures across the time. There was significant improvement on lip measurement as well. The participants’ satisfaction level was 8.5 (±1.20)/10 with the intervention. Conclusions: The Kabat intervention integrated with facial expressive and functional exercises demonstrated significant improvement in impairments and functional level. Large effect sizes and high level of participants’ satisfaction indicated clinical relevance of the intervention.